Effects of Ramadan intermittent fasting on performance, physiological responses, and bioenergetic pathway contributions during repeated sprint exercise - Özbay, Serhat; Ulupınar, Süleyman; Gençoğlu, Cebrail; Ouergui, Ibrahim; Öget, Furkan; Yılmaz, Hasan Hüseyin; Kishalı, Necip Fazıl; Kıyıcı, Fatih; Asan, Selim; Uçan, İzzet; Ardigò, Luca Paolo (Frontiers in Nutrition, 2024)
Introduction: This investigation aims to elucidate the impact of Ramadan intermittent fasting on performance, physiological responses, and bioenergetic pathway contributions during repeated sprints. Methods: Fourteen active male Muslim athletes (age = 22.4±1.8 years, body weight = 69.5±3.8 kg, height = 176±5.1 cm) executed a repeated sprint protocol, consisting of ten 20-meter sprints with 15-second passive recovery intervals, during both fasting and non-fasting conditions. The fasting session was conducted after a 12-14 hour fast following Sahur (the pre-dawn meal during Ramadan). In contrast, the non-fasting session occurred before the Ramadan fasting period began, during the same hours of the day, at a time when fasting was not yet required for the athletes. Bioenergetic pathway contributions during repeated sprints were quantified using the PCr-LA-O2 method. Results: The mean sprint time during fasting sessions was 3.4±0.3 seconds compared to 3.3±0.2 seconds in non-fasting sessions, indicating a trend approaching the threshold of significance for slower times in the fasted state (p=0.052, effect size (ES) = 0.34). In terms of bioenergetic contributions, the total metabolic energy expenditure (TEE) was slightly lower during fasting sessions (236.5±22 kJ) compared to non-fasting sessions (245.2±21.7 kJ), but this difference was not statistically significant (p=0.102, ES = 0.40). Similarly, metabolic energy expenditure per sprint was 23.7±2.2 kJ in fasting conditions compared to 24.5±2.2 kJ in non-fasting conditions (p=0.106, ES=0.35). The oxidative energy contribution did not differ significantly between fasting (34.2±4.1 kJ) and non-fasting conditions (34.2±4.1 vs. 35.5±5.2 kJ; p=0.238, ES=0.28). Similarly, lactic (60.4±7.6 vs. 59.2±8.3 kJ; p=0.484, ES=0.15); and alactic (149.3±19.9 vs. 143±21.5 kJ; p=0.137, ES=0.30) energy contributions showed no significant differences between the fasting and non-fasting sessions. The percentage of performance decrement (Pdec) and the percentage contributions of oxidative, lactic, and alactic pathways to the total energy expenditure did not differ significantly between the fasting and non-fasting conditions, indicating a similar bioenergetic profile across both conditions. Conclusion: The present findings indicate no significant differences in performance metrics and metabolic outcomes between fasted and non-fasted states. Future assessments with longer duration and higher intensity protocols may provide further insights.